La storia dell’arte dopo la fine della storia dell’arte - Luca Marchetti (Rivista di Estetica, 2021)
Danto’s philosophy of history of art has undergone several transformations. It is possible to distinguish three “phases”: in the first, history is considered an a posteriori construction (see Analytical Philosophy of History). In the second phase, history becomes an internal development within art itself. In this case, with the end of history, art dissolves into its own philosophy (see The Philosophical Disenfranchisement of Art). In the third phase, history is still an internal development, but now, with the end of history, art and philosophy become independent of each other (see After the End of Art). This essay focuses on two issues: first, on the difficulties of an art history after the end of the history of art; secondly, for what reasons Danto claims that the history of art is ended. Danto has explained the “political” reasons for this choice, namely the attempt to free art from the repressive and disenfranchising moves of philosophy. This essay aims to outline the epistemic reasons: the history of art “must” end, because only on this condition is an essentialist definition of art really possible.